Synthesis of Educational Aspirations of Indigenous Ethnic Groups in Indonesia: A Systematic Literature Review Based on Scopus and Google Scholar (2020–2025) - Rahawarin, Benediktus; Nurhattati, Nurhattati; Kamaludin, Kamaludin (FKIP - Universitas Riau, 2026)
Education for Indigenous communities in Indonesia holds profound significance, serving not only as a means of knowledge transfer but also as a medium for cultural identity preservation and social empowerment. This study synthesizes research on the educational aspirations of Indigenous peoples in Indonesia during 2020–2025 by examining trends, patterns, and scholarly contributions. Using a Systematic Literature Review (SLR) based on the PRISMA 2020 protocol, 35 articles from Scopus and Google Scholar were analyzed through thematic coding and bibliometric mapping with VOSviewer. Results show a significant increase in publications after 2020, focusing on two domains: education and policy. In education, findings reveal a shift from access-focused issues to socio-cultural dimensions of learning, highlighting the influence of social, cultural, and spiritual factors and the rise of community-based approaches integrating Indigenous Knowledge Systems (IKS) with modern pedagogy under an eco-cultural framework. In policy, challenges include weak regulation, limited funding, and insufficient integration of local knowledge and mother tongues into the national curriculum. Addressing these issues requires culturally equitable policies through recognition of Indigenous knowledge, multilingual education, and active community participation. This synthesis emphasizes that advancing Indigenous educational aspirations depends on the synergy between culturally grounded practices and inclusive, decentralized, epistemically diverse public policies.